Outbreak of Fusarium oxysporum infections in children with cancer: an experience with 7 episodes of catheter-related fungemia - Fabianne Carlesse; Anna-Paula C. Amaral; Sarah S. Gonçalves; Hemilio Xafranski; Maria-Lucia M. Lee; Victor Zecchin; Antonio S. Petrilli; Abdullah M. Al-Hatmi; Ferry Hagen; Jacques F. Meis; Arnaldo L. Colombo (Antimicrobial Resistance and Infection Control, 2017)
Abstract Background Fusarium species are widely spread in nature as plant pathogens but are also able to cause opportunistic fungal infections in humans. We report a cluster of Fusarium oxysporum bloodstream infections in a single pediatric cancer center. Methods All clinical and epidemiological data related to an outbreak involving seven cases of fungemia by Fusarium oxysporum during October 2013 and February 2014 were analysed. All cultured isolates (n = 14) were identified to species level by sequencing of the TEF1 and RPB2 genes. Genotyping of the outbreak isolates was performed by amplified fragment length polymorphism fingerprinting. Results In a 5-month period 7 febrile pediatric cancer patients were diagnosed with catheter-related Fusarium oxysporum bloodstream infections. In a time span of 11 years, only 6 other infections due to Fusarium were documented and all were caused by a different species, Fusarium solani. None of the pediatric cancer patients had neutropenia at the time of diagnosis and all became febrile within two days after catheter manipulation in a specially designed room. Extensive environmental sampling in this room and the hospital did not gave a clue to the source. The outbreak was terminated after implementation of a multidisciplinary central line insertion care bundle. All Fusarium strains from blood and catheter tips were genetically related by amplified fragment length polymorphism fingerprinting. All patients survived the infection after prompt catheter removal and antifungal therapy. Conclusion A cluster with, genotypical identical, Fusarium oxysporum strains infecting 7 children with cancer, was most probably catheter-related. The environmental source was not discovered but strict infection control measures and catheter care terminated the outbreak.